Marketing major sports venues - the Amsterdam ArenA case - Santini, Andrea (Henry Stewart Talks, 2008)
The marketing of major sport venues: process and main phases, The complexity of marketing major sport venues, The relation between marketing & sales and the legal, operational and management structure of a large sport venue, The case of the Amsterdam ArenA, The development of large entertainment areas, the ArenA Boulevard
Archived at 2022/04/04